Influence Leadership Head School to Performance High School Teacher in Minahasa Regency - Sumual, Tinneke E. M.; Sumual, Herry; Dondokambey, Robby; Dotulong, Reza A W; Ratumbuisang, Keith F (JR Education, 2024)
This research was conducted to determine the influence of leadership School Principals on the Performance of Middle School Teachers in Minahasa Regency. There are 38 state junior high schools and private with a total of 581 teachers. These junior high schools are spread across 14 sub-districts. A study done including study quantitative causality with technique collection data use method libraries research ie assessment And analysis return to research previous Which related with influence Principal leadership on teacher performance. The research results show that the leadership Head School proved their connection positive And influential in a way significant to the Performance of the Teacher.